Testing how environmental variables affect the survival of freshwater turtle nests and hatchlings using artificial nests and dummy hatchlings - J. Lanszki; T. G. Molnár; T. Erős; G. Ónodi; Z. Lanszki; J. J. Purger (Scientific Reports)
Abstract The European pond turtle (Emys orbicularis) is a wide-ranging, long-living freshwater species with low reproductive success, mainly due to high predation pressure. We studied how habitat variables and predator communities in near-natural marshes affect the survival of turtle eggs and hatchlings. We followed the survival of artificial turtle nests placed in marshes along Lake Balaton (Hungary) in May and June as well as hatchlings (dummies) exposed in September. We found that the fewest nests remained intact in the least disturbed, most extensive area with the largest turtle population without predator control. Hatchlings, compared to nests had a significantly higher probability of survival. The density of carnivore dens indicated the negative influence on the number of exposure days, while marsh vegetation coverage was unrelated. The role of carnivores, especially the red fox (Vulpes vulpes) in the predation of nests was more significant, while predation by corvids (Corvidae) and wild boar (Sus scrofa) increased for the hatchlings. Predation by mammals increased with the limited availability of dry terrestrial surfaces suitable for laying eggs and with distance to water. Our multifactorial analyses highlight the need for targeted conservation efforts to improve the reproductive success of turtles in these ecologically sensitive environments.